Reconstruction of a Locally Rough Interface and the Embedded Obstacle with the Reverse Time Migration (Communications in Computational Physics, 2025)
Consider the inverse problem of time-harmonic acoustic scattering by anunbounded locally rough interface with bounded obstacles embedded in the lowerhalf-space. An extended reverse time migration (RTM) is proposed to simultaneouslyreconstruct the locally rough interface and embedded obstacles. By constructing amodified Helmholtz-Kirchhoff identity associated with a planar interface and a mixedreciprocity relation, we propose two new imaging functionals with using both thenear-field and far-field measurements. It is shown that the imaging functionals alwayspeak on the local perturbation of the interface and the embedded obstacle. Thus, thetwo imaging functional can be used to reconstruct the location and shape of the roughsurface and the embedded obstacle. Numerical examples are presented to demonstratethe effectiveness of the method.
Keywords: Inverse acoustic scattering; locally rough interfaces; embedded obstacles; reverse time migration.